PINEAPPLE JAM PHYSICOCHEMICAL AND SENSORY EVALUATION WITH ADDED PINEAPPLE PEEL - dos Santos, Bruna Aparecida; Teixeira, Flávia; Soares, Jaqueline Machado; do Amaral, Luane Aparecida; de Souza, Gabriel Henrique Oliveira; de Almeida, Tainá da Silva Fleming; Schiessel, Dalton Luiz; dos Santos, Elisvânia Freitas; Novello, Daiana (International Journal of Research -GRANTHAALAYAH, 2020)
The aim of this research was to evaluate the effect of pineapple peel (PP) addition on pineapple jam physicochemical and sensory characteristics. Five pineapple jam formulations were prepared: standard F1 (0% PP) and the others added 2.5% (F2), 5% (F3), 7.5% (F4) and 10% (F5) of PP. The results of sensory analysis indicated the feasibility of adding PP in pineapple jam, especially up to a level of 5%. The addition of PP increased soluble solids, titratable acidity, sugars, moisture, dietary fiber, phenolic compounds and antioxidant capacity. Also, it increased the values for a* and decreased for L* and b*. The use of up to 5% PP in jam should be encouraged as it can improve physicochemical characteristics and maintain sensory acceptability of the product. It also reduces negative effects of organic waste disposal on the environment.